2002
DOI: 10.1002/lsm.10055
|View full text |Cite
|
Sign up to set email alerts
|

Holmium: YAG laser‐induced liquid jet knife: Possible novel method for dissection

Abstract: The laser-induced liquid jet has excellent potential as a new tool for removing soft tissue without damaging vital structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Therefore, the laser pulse forms a transient vapor bubble in the water flow, and the three‐dimensional expansion of the confined vapor bubble is used to drive a one‐dimensional liquid jet through a fine nozzle, thus generating a high‐velocity pulsed jet of microliter order . We have already reported that tissue penetration depth depends on initial velocity and pressure, which can be controlled by the laser energy, stand‐off distance, and nozzle (aspect) ratio . In the present experiment, we found that when using the endoscopic pulsed jet device, tissue penetration also depended on those same factors, despite differences in structure.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Therefore, the laser pulse forms a transient vapor bubble in the water flow, and the three‐dimensional expansion of the confined vapor bubble is used to drive a one‐dimensional liquid jet through a fine nozzle, thus generating a high‐velocity pulsed jet of microliter order . We have already reported that tissue penetration depth depends on initial velocity and pressure, which can be controlled by the laser energy, stand‐off distance, and nozzle (aspect) ratio . In the present experiment, we found that when using the endoscopic pulsed jet device, tissue penetration also depended on those same factors, despite differences in structure.…”
Section: Discussionsupporting
confidence: 49%
“…8,15 We have already reported that tissue penetration depth depends on initial velocity and pressure, which can be controlled by the laser energy, stand-off distance, and nozzle (aspect) ratio. 28,29 In the present experiment, we found that when using the a b endoscopic pulsed jet device, tissue penetration also depended on those same factors, despite differences in structure.…”
Section: W E Have Successfully Shown That a Pulsed Jet Device Can Be mentioning
confidence: 48%
“…The liver parenchyma was dissected along with Glisson's sheaths without vessel damage, and there were neither signs of thermal damage nor degeneration of hepatocytes. Water jet dissection may be dependent on the physical properties of the target tissue because it is well known that membranous structures are resistant to water jet applications [17,34]. The results of the present investigation on breaking strength may explain the mechanism of dissection capability and tissue selectivity of the ADPJ in view of the tissue-specific physical properties.…”
Section: Discussionmentioning
confidence: 72%
“…As a dissection device for microsurgical use, we have already demonstrated that this pulsed LILJ has the sufficient ability to preserve blood vessels compared with a conventional water jet. We have also demonstrated that the jet velocity, which is linearly related to penetration depth in artificial tissue, can be controlled by varying the laser energy, standoff distance (defined as the distance between the tip of the optical fiber and the nozzle; L), and the tapering of the nozzle [25,26,28]. However, management (reduction) of the accompanying shock wave [27][28][29][30][31][32], as well as evaluation of dissection quality under an endoscopic environment, must occur before this system can be applied for clinical use.…”
Section: Introductionmentioning
confidence: 97%
“…To solve those problems, we have reduced the water requirement via the application of pulsed holmium: yttrium-aluminum-garnet (Ho:YAG) laser-induced liquid jet (LILJ) system [24][25][26][27][28]. This technology was initially developed to enhance the effect of fibrinolytics during the treatment of acute cerebral embolism, this being achieved both by mechanical penetration of the thrombus and by delivery of the drugs into the same [24,29,30].…”
Section: Introductionmentioning
confidence: 99%